Global supply chain of biomass use and the shift of environmental welfare from primary exploiters to final consumers. (15th October 2020) - Ji, Xi; Liu, Yifang; Meng, Jing; Wu, Xudong
Highlights: The biomass use from primary supply to final consumption via global supply chain is established. The shift of environmental welfare from biomass-exporting nations to biomass-importing nations is discussed. International transfer of biomass use is 87% of global total biomass exploitation. The United States is a leading net importer and Brazil is a major net exporter. A global perspective is offered for policy makers towards biomass development. Abstract: With the increasingly frequent interregional trade that leads to the geographical separation of production and consumption, the invisible shift of the environmental welfare bestowed by biomass use is brought to attention. Using a systems embodiment accounting model, this study tracked the dynamic process of interregional transfer of biomass use from primary supply to final consumption via the global supply chain. The results reveal that biomass use embodied in global trade is 87% of total global biomass exploitation. Moreover, the intermediate trade volume is 1.7 times higher than the final trade volume. In terms of biomass use, the United States, South Korea, mainland China, Japan, and the United Kingdom are revealed as the five leading net importers and also the main final consumers. Brazil, India, Cyprus, Indonesia, and Latvia are demonstrated to be the top five net exporters and also the main exploiters of biomass resources. The biomass self-sufficiency rate by source and that by sink for each country are then discussed. The outcome shows that through the channels of global supply chain, the shift of environmental welfare from biomass-exporting nations to biomass-importing nations occurs along with interregional trade. For Brazil and India, we suggest that they should strike a balance between economic revenues and long-term sustainability. Regarding the consumption-oriented nations such as the United States, an increase in the energy efficiency of high value-added industries is recommended.